Space-occupying cerebellar infarction: complications, treatment, and outcome - Neugebauer, Hermann; Witsch, Jens; Zweckberger, Klaus; Jüttler, Eric (Neurosurgical focus, 2013)
Space-occupying brain edema is a frequent and one of the most dreaded complications in ischemic cerebellar stroke. Because the tight posterior fossa provides little compensating space, any space-occupying lesion can lead to life-threatening complications through brainstem compression or compression of the fourth ventricle and subsequent hydrocephalus, both of which may portend transtentorial/transforaminal herniation. Patients with large cerebellar infarcts should be treated and monitored very early on in an experienced stroke unit or (neuro)intensive care unit. The general treatment of ischemic cerebellar infarction does not differ from that of supratentorial ischemic strokes. Treatment strategies for space-occupying edema include pharmacological antiedema and intracranial pressure-lowering therapies, ventricular drainage by means of an extraventricular drain, and suboccipital decompressive surgery, with or without resection of necrotic tissue. Timely escalation of treatment is crucial and should be guided by clinical and neuroradiological rationales. Patients in a coma after hydrocephalus and/or local brainstem compression may also benefit from more aggressive surgical treatment, as long as the conditions are reversible. Contrary to the general belief that outcome in survivors of space-occupying cerebellar stroke is usually good, recent studies suggest that for many of these patients, the long-term outcome is not good. In particular, advanced age and additional brainstem infarction seem to be predictors for poor outcome. Further trials are necessary to investigate these findings systematically and provide better selection criteria to help guide decisions about surgical therapies, which should always be carried out in close cooperation among neurointensive care physicians, neurologists, and neurosurgeons.
Gesehen am 08.12.2021